2013
DOI: 10.7314/apjcp.2013.14.3.1681
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Expression, Serum and Salivary Levels of IL-10 in Patients with Head and Neck Squamous Cell Carcinoma

Abstract: Background: Head and neck SCC is a common cancer related to various factors. IL-10, a pleiotropic cytokine produced by macrophages, T-helper-2 cells, and B lymphocytes, is thought to play a potential pathogenetic or therapeutic role in a number of human conditions, such as inflammation, autoimmunity and cancer. The present study was designed to evaluate the relation between tissue expression, serum and salivary levels of IL-10 in head and neck squamous cell carcinomas (HNSCCs) and their correlation with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
6
18
1
3
Order By: Relevance
“…These results are consistent with other studies regarding IL-10 status in OSCC, although these studies have analyzed the IL-10 protein and mRNA levels in OSCC tumor tissues (35,36). Moreover, Hamzavi et al studied and compared the tissue expression, serum, and salivary levels of IL-10 and found no correlation among them in either controls or OSCC subjects (30), which reflects different levels of regulation of this cytokine in different compartments of the body. Alhamarneh et al found significantly higher serum levels of IL-10 in advanced stages of head and neck squamous cell carcinoma except oral cavity tumors (37).…”
Section: Cancer Investigationsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with other studies regarding IL-10 status in OSCC, although these studies have analyzed the IL-10 protein and mRNA levels in OSCC tumor tissues (35,36). Moreover, Hamzavi et al studied and compared the tissue expression, serum, and salivary levels of IL-10 and found no correlation among them in either controls or OSCC subjects (30), which reflects different levels of regulation of this cytokine in different compartments of the body. Alhamarneh et al found significantly higher serum levels of IL-10 in advanced stages of head and neck squamous cell carcinoma except oral cavity tumors (37).…”
Section: Cancer Investigationsupporting
confidence: 88%
“…A study conducted by Kaskas et al showed contradictory results and reported significantly lower serum levels of IL-13 in head and neck squamous cell carcinoma as compared to normal healthy controls (29). It has also been shown in other studies as well, that the alterations in cytokine phenotypes in the patients' oral lesions are not necessarily reflected in the peripheral blood (serum/plasma; 30,31). This discrepancy could be explained in several ways.…”
Section: Cancer Investigationmentioning
confidence: 70%
“…In a survey of the salivary-cytokine literature, we find that the majority involve local conditions arising close to the salivary glands, such as oral inflammation [30,31] or head neck or oral, cancer [32,33]. Our observed dissociation of the cytokine response between the circulating pattern and that in the saliva, moreover, is neither unprecedented nor implausible.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, it was also observed that in patients with hepatocellular carcinoma (HCC), IL-10 contributed to the Treg-mediated suppression of the cytotoxic activities and IFN-γ production by γδ T cells (Yi et al, 2013). Finally, conflicting results were obtained regarding the association between serum concentrations of IL-10 and head and neck squamous cell carcinoma (Melinceanu et al, 2011;Mojtahedi et al, 2012;Hamzavi et al, 2013) and HCC (Jang et al, 2012;Welling et al, 2012).…”
Section: Expression Of Il-10 In Patients With Cancermentioning
confidence: 89%